A STUDY OF STRATEGIES FOR TRANSLATING SHORT POEMS FROM CHINESE TO THAI: A CASE STUDY OF TRANSLATING 100 SHORT POEMS BY ZENG XIN - Prapagorn, Puthep (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The objective of this research article is to study the techniques used in translating short poems by Zeng Xin (Mr. Kriangkrai Sattrawong) from Chinese into Thai. The translation was conducted by Mr. Niranon Nakhasuriyan. This research is a qualitative study and a document analysis research. The main source of data is the book containing 100 short poems titled 'Zeng Xin Xiao Shi Yi Bai Shou.' The researcher adopted a translation theory based on the concept of centuple filtering, as well as related research as a framework. The sample group in this study consisted of translated short poems not exceeding 6 lines by Zeng Xin, translated into polite verse by Niranon Nakhasuriyan. The research findings reveal that the most frequently employed technique involves adding words or phrases, totaling 81 instances. The second most common technique is reordering words or phrases, with 24 instances. Following that is the technique of reducing words or phrases, with 12 instances, and direct translation with 7 instances. Additionally, other techniques were also identified, including word variations or repetition, amounting to 5 instances. Among the original 100 poems, there are 28 translated poems in Thai utilized more than one translation technique. The researcher also found that a combination of direct translation and other translation methods was employed to preserve the meaning of the original poems and maintain the aesthetic appeal in the translated versions. The researcher discovered that the factors influencing the selection of these translation techniques include: 1. Factors from the original short poems, 2. Factors from the translator, and 3. Factors related to the characteristics of the poems and the publishing process.